Biomorphic Ceramics for Drug Delivery in Bone Tissue Regeneration - Diaz-Rodriguez, Patricia; Landin, Mariana (Current Pharmaceutical Design, 2017)
Incorporating therapeutic molecules into biomorphic ceramics for in situ drug release can be used to generate novel systems for tissue regeneration. These systems couple the complex hierarchical porous structures of biomorphic ceramics with the therapeutic activity of drugs. There are a large number of natural precursors available to be used as templates to obtain biomorphic silicon carbide ceramics. Additionally, different drug loading techniques can be used for these systems. The high versatility in structures and drugs allows the selection of the right structure-drug fit in each case according to the tissue needs. This paper reviews the utility of biomorphic ceramics for tissue engineering as well as their use for local drug release.
Keywords: biomimetic